Respon Pertumbuhan dan Hasil Cabai Rawit (Capsicum frutescens L.) Terhadap Pemberian Trichokompos dan NPK Pada Tanah Ultisol - Edy Prastya; Gusti Muhammad Sugian Noor; Ahmad Kurnain (Agroekotek View, 2018)
This research is to know the effect of interaction and the best combination of giving trichokompos and NPK on growth and yield of cayenne pepper (Capsicum frutescens L.). This research used polybag with factorial randomized block design (RAK) of two factors. The first factor was 4 levels of trichokompos dose treatment (T): t1 = 150 gram / polybag, t2 = 300 gram / polybag, t3 = 450 gram / polybag, t4 = 600 gram / polybag, and the second factor is 4 levels dose treatment of NPK (N) n0 = 0 gram / polybag, n1 = 60 gram / polybag, n2 = 120 gram / polybag, n3 = 180 gram / polybag. The result of the research showed trichokompos and NPK giving interaction effect on plant height 14 hst, while at plant height 21, 28, 35, and 42 hst, number of branch books, the number of fruit crops, and the weight of fruit crops, interaction of trichokompos fertilizer and NPK has no significant effect. The single treatment of NPK dosage influenced the number of branch book, the number of fruit crops, and the weight of the crops, while the single trichocompos treatment did not affect all observed variables.